Regulatives Garden and Flowers in the Epistolary Texts by Lesia Ukrainka (Linguostylistic Studies, 2017)
The article considers individually-emphasized images-regulatives garden and flowers in Lesia Ukrainka’s artistic and epistolary texts. The author accentuates attention on the basic contexts of their explication in the poetess’ correspondence heritage. The study highlights the peculiarities of modeling the semantic space of these micro semantic fields. The emphasis is laid on the typological comparative explication of regulatives garden and flowers as compared to forest, in particular at the level of their semanic field hierarchy. The in-depth analysis has revealed the most productive functional stylistic features of their actualization. The key findings of the study suggest that they are determinative for epistolary linguistic creativity of Lesia Ukrainka and contribute to understanding the national linguistic image of the world in her individual style. The conclusions of the study elucidate their role in self-portraiture of the addressee.
Keywords: regulatives garden and flowers; microfield; epistolary text; language creation